2018
DOI: 10.1002/ijfe.1686
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the nexus between oil and exchange rate in the major emerging markets—The timescale analysis

Abstract: This paper investigates the interrelationship between Brent oil price and exchange rate in 10 emerging markets of East Europe, Asia, Africa, and South America. For computational purpose, we apply two innovative methodologies—wavelet coherence and phase difference that are capable of observing different frequency scales. Wavelet coherence results suggest that strong coherence is present during world financial crisis (WFC) in the oil‐exporting countries and in majority of the oil‐importing countries. Phase arrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The findings indicate that the underlying relationship between oil prices and stock returns get stronger in a period of high volatility. More recently, Živkov, Njegić, and Balaban (2019) examine the transmission mechanism of oil price shocks towards exchange rates, using oil prices and exchange rate data from 10 emerging market economies of Asia, Africa, East Europe and South America. They find strong ‘coherence’ between Brent oil prices and exchange rates during the financial crisis period in both oil‐exporting countries and in many of the major oil‐importing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings indicate that the underlying relationship between oil prices and stock returns get stronger in a period of high volatility. More recently, Živkov, Njegić, and Balaban (2019) examine the transmission mechanism of oil price shocks towards exchange rates, using oil prices and exchange rate data from 10 emerging market economies of Asia, Africa, East Europe and South America. They find strong ‘coherence’ between Brent oil prices and exchange rates during the financial crisis period in both oil‐exporting countries and in many of the major oil‐importing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following the existing studies (e.g., Yang et al, 2016; Gallegati, 2012; Živkov et al, 2019a, 2019b), we use discrete wavelet transform to analyse interdependence and financial contagion among exchange rates. For wavelet transformation, non-decimated orthogonal Maximum Overlap Discrete Wavelet Transform (MODWT) decomposing the data to 8 levels is used.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that lower‐upper and upper‐lower tail dependence of the US dollar and oil are significantly negative. Živkov, Njegić, and Balaban (2019) used wavelet coherence and phase difference methodologies to study the correlation between oil and exchange rate in 10 major countries.…”
Section: Literature Reviewmentioning
confidence: 99%